Conversão da união estável em casamento - Madeira Filho, Ibrahim Fleury de Camargo (2011)
The Federal Constitution of 1988, in reference to the Family Law, innovated in disposing the Article 226, 3rdparagraph: For effect of protection of the State, it is recognized the common-law marriage between man and woman as a familiar entity, and the law should facilitate its conversion into civil marriage . We have concentrated on the second part of this constitutional precept and only the common-law marriage between man and woman. There have been new judgments by the Brazilian Federal Supreme Court (STF) based on this modification. Although the Constitution has oriented to the law enactment, that facilitated the conversion of the common-law marriage, between man and woman, into civil marriage, the legislators haven`t accomplished their mission, or at least, they haven`t done it properly. Not even with the enactment of the law n. 9.278 from 05-10-1996, nor the Civil Code from 2002, article n. 1.726. There some bills about the theme mentioned above that have been examined by the National Congress. These omissions on the laws cause many problems and the Justice Court-inspecting Authority of each State has tried to supply them. We have observed, since antiquity, there is a concern about formalizing marriages among the couples who have informal relationships. Moreover, according to the Brazilian Geography and Statistics Institute (IBGE) more than 1/3 (one-third) of the Brazilian couples haven`t got the civil registry to legalize their common-law marriage. This constitutional law being examined has been created for their assistance. We consider the conversion of the common-law marriage into civil marriage similar to the conversion of religious marriage into civil marriage. Our research has involved comparative law and revealed many similarities between Brazilians Laws and those of other nations, but they have less detail and are not expressed at the Constitutional level, as seen in Brazil, where it is established that the law should facilitate the conversion of the common-law marriage into civil marriage. We have indicated the possible reasons, judicial and practical, to think about the right to convert common-law marriage into civil marriage; the indispensable constitutional and legal requirements for it; the adequate procedures to be within the constitutional law; beyond the effects derived from exercising of this right